2011
DOI: 10.1007/s10532-011-9483-z
|View full text |Cite
|
Sign up to set email alerts
|

Mercury bioremediation by mercury accumulating Enterobacter sp. cells and its alginate immobilized application

Abstract: The effective microbial remediation of the mercury necessitates the mercury to be trapped within the cells without being recycled back to the environment. The study describes a mercury bioaccumulating strain of Enterobacter sp., which remediated mercury from the medium simultaneous to its growth. The transmission electron micrographs and electron dispersive X-ray analysis revealed the accumulation of remediated mercury as nano-size particles in the cytoplasm as well as on the cell wall. The Enterobacter sp. in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 35 publications
1
15
0
1
Order By: Relevance
“…Therefore the reported biouptake capacity of our bacterial strains (C. muytjensii, E. helveticus, and C. amalonaticus) is mainly explained by their abilities to biouptake mercury by storing and absorbing it in their cytoplasm hence less mercury levels were reported after the removal of bacterial cells from the filtrate used for measurement. Our suggestion coincides with the study of Sinha and Khare (2012) as they reported similar mechanism of bio-uptake for Enterobacter sp.…”
Section: Za3supporting
confidence: 93%
See 1 more Smart Citation
“…Therefore the reported biouptake capacity of our bacterial strains (C. muytjensii, E. helveticus, and C. amalonaticus) is mainly explained by their abilities to biouptake mercury by storing and absorbing it in their cytoplasm hence less mercury levels were reported after the removal of bacterial cells from the filtrate used for measurement. Our suggestion coincides with the study of Sinha and Khare (2012) as they reported similar mechanism of bio-uptake for Enterobacter sp.…”
Section: Za3supporting
confidence: 93%
“…The major advantage of bioremediation either by volatilization or biosorption is to uptaking and detoxifying Hg(II) and organic Hg species to elemental Hg, thereby preventing food chain accumulation (Sinha and Khare, 2012;Wagner-Dobler, 2013). To prevent accumulation and facilitate volatilization, after bacterial uptake, incineration might be the best solution (Xu et al, 2015).…”
Section: Waste Management Of Mercury From the Spent Fluorescent Lampsmentioning
confidence: 99%
“…Free cells of Enterobacter decreased almost 66% of initial mercury concentration in aqueous solution during 48 h of incubation when exposed to initially 5 mg L −1 mercury. However, its alginate immobilized form was more efficient with about 95% removal under the same conditions . The maximum mercury removal by calcium alginate immobilized B. cereus biomass was 98.9%, which was achieved after 120 h of incubation under 10 mg L −1 initial mercury concentration.…”
Section: Resultsmentioning
confidence: 89%
“…The immobilized cells can be reused for up to four consecutive cycles of Hg‐detoxification experiments as reported by Amin and Latif, . The immobilization of E. cloacae and its potential to remediate mercury has also been evaluated as a complete removal of Hg +2 from mercury enriched media . So in conclusion, the immobilization of culture is better technique as compared to the usage of free cells for bioremediation of mercury after 8 days at large scale.…”
Section: Discussionmentioning
confidence: 99%